A REVIEW OF THE RIGHTS OF THE SECOND WIFE WHICH THE MARRIAGE IS CONDUCTED WITHOUT THE CONSENT OF THE FIRST WIFE TO DEMAND THE OBLIGATION OF THE HUSBAND IN THEIR LAW OF DIVORCE - Sukam Permana, Yana (Awang Long Law Review, 2021)
Divorce is the breaking of the marriage rope between husband and wife in a family relationship. So that the divorce must be preceded by a marriage that is legal according to the laws of each religion and belief. If the marriage is illegal or does not have legal force such as the case in the East Jakarta Religious Court decision Number 495/Pdt.G/1996/PA-JT, then the marriage is about to break up with the filing for divorce, then the judge should reject the divorce suit. because the second marriage was carried out without the permission or consent of the first wife. Even though that permission or agreement is a condition for every second marriage for which permission is to be asked to the Religious Court. A second marriage that is carried out without the permission of the Religious Court is invalid or has no legal force as stated in article 4 of Law Number 1 of 1974 concerning Marriage and Articles 40 and 44 of the Republic of Indonesia Government Regulation. 9 of 1975 concerning the Implementation of the Marriage Law No. 1 of 1974 and article 56 verses 1 and 3 of the Compilation of Islamic Law. Thus it is obligatory for a husband who wants to marry both of them to first ask for permission to the Religious Court.